Challenges and opportunities for digital convergence of TV: audience measurement in the digital era - Smolak-Lozano, Emilia (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
The research on television market and audience has been so far dominated by a telemetric system operating within a determined panel in the longitudinal manner. Nevertheless, the rise of digital era marked by the growing consumption of audiovisual content and TV in the Internet via VOD systems, subscription services, streaming etc. has changed the way the TV audience should be measured and tackled in order to deliver the significant data to advertisers. The digital services and therefore the online ads consumption are forcing the telemetric companies to re-design their methodology and measurement services. This thus requires not only new measurement methods and sample designs or research planning but also demonstrate new challenges and requirements starting from technical aspects and finishing on social and economic ones. Therefore, it is of great interests to find out how digital TV audience era is changing the way telemetric services are designed and conducted globally and at Polish market. The study attempts to find out how the TV audience measurement service is responding to the changes caused by digitalisation, which challenges and requirements have to be met in order to approach the issue of digitalisation of TV market in terms of the research planning and methodology. Finally, the present research pretend to determine and describe how the global market, and the Polish one in particular, perceives the services offered by Nielsen Audience Measurement. The research includes the series of individual semi-structured online individual interviews with managers and board of directors of the company as well as digital ads ratings department in Poland and headquarters in Switzerland. The results demonstrate the key changes, opportunities and challenges resulted from the digitalisation of TV consumption as perceived by management board, the company’s strategy towards digital convergence and the estimation of the needs of new markets and audiences on the course of the digital transformation.

Badania rynku telewizyjnego i widowni były dotychczas zdominowane przez system telemetryczny, który współpracuje z panelem w procesie badań longituidalnych. Jednak rozwój ery cyfrowej naznaczony rosnącym zużyciem treści audiowizualnych i telewizyjnych w Internecie lub za pośrednictwem systemów VOD, usług subskrypcyjnych, transmisji itp. zmienił sposób pomiarów widowni telewizyjnej prowadzonych w celu uzyskania danych znaczących dla reklamodawców. Usługi cyfrowe, a zatem konsumpcja reklam internetowych, zmusza firmy telemetryczne do wprowadzenia zmian w metodologii i usług pomiarowych w celu wyeliminowania problemów metodologicznych i kwestii statystycznych, jakie pojawiają się w Internecie. Badania telewizyjne w dobie cyfrowej wymagają nie tylko nowych metod pomiarowych i przykładowych projektów lub innego planowania badań, ale także muszą stawiać czoła nowym wyzwaniom i wymaganiom dotyczącym aspektów technicznych, jak również aspektów społecznych i ekonomicznych. Wskutek tych tendencji, interesującym zagadnieniem jest zbadanie jak era odbiorców telewizji cyfrowej zmienia sposób projektowania i wykonywania usług telemetrycznych na całym świecie i na rynku polskim. Badanie zawarte w tym artykule ma na celu odkrycie, w jaki sposób usługa pomiaru widowni telewizyjnej reaguje na zmiany spowodowane digitalizacją, jakie wyzwania i wymagania należy spełnić, aby rozwiązać problem cyfryzacji rynku telewizyjnego w zakresie planowania badań i metodologii, a na koniec jak światowy i polski rynek postrzega usługi oferowane przez sektor telemetryczny. Badanie obejmuje serię indywidualnych, częściowo ustrukturyzowanych wywiadów online z menedżerami i zarządami firmy reprezentującej badania telemetryczne, a także z działem cyfrowej oceny reklam w Polsce i centrali w Szwajcarii. Wyniki pokazują kluczowe zmiany, szanse i wyzwania wynikające z cyfryzacji konsumpcji telewizyjnej zgodnie z percepcją rady dyrektorów, a także strategię firmy na rzecz konwergencji cyfrowej i wreszcie oszacowanie potrzeb nowych rynków oraz odbiorcy w trakcie transformacji cyfrowej.
Szanse i wyzwania konwergencji cyfrowej telewizji: pomiary widowni w erze komunikacji cyfrowej
Keywords: Television; TV audiences; telemetry; TV audience measurement; digital TV; telewizja; widownia telewizyjna; telemetria; pomiar widowni telewizyjnych; cyfryzacja; era cyfrowa